2012
DOI: 10.7202/1009083ar
|View full text |Cite
|
Sign up to set email alerts
|

Valeurs et attitudes des jeunes travailleurs à l’égard du travail au Québec : une analyse intergénérationnelle

Abstract: Cet article vise à évaluer le degré de différenciation des valeurs et attitudes relatives au travail des jeunes travailleurs québécois en regard de celles des travailleurs d’un âge plus avancé. Pour ce faire, nous analysons les trois dimensions essentielles du rapport au travail, à savoir la centralité du travail, sa finalité principale et les attitudes à l’égard des normes managériales dominantes. Nos analyses sont fondées sur les données d’une enquête réalisée en 2007 sous forme de questionnaire aupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 10 publications
(2 reference statements)
0
9
1
14
Order By: Relevance
“…In contrast to these research findings, a limited number of studies have found that educational attainment is either not related or negatively related to work centrality (Bal and Kooij, 2011;Harpaz and Fu, 1997;Warr, 2008). For example, Mercure, Vultur and Fleury (2012) find that, among workers in Quebec, absolute and relative work centrality are the lowest among those with low educational attainment, the highest among those with post-secondary attainment and intermediate among those with academic degrees. Family centrality has been found to be negatively correlated with education (Kuchinke et al, 2011;Sharabi, 2000).…”
Section: Educationmentioning
confidence: 90%
See 3 more Smart Citations
“…In contrast to these research findings, a limited number of studies have found that educational attainment is either not related or negatively related to work centrality (Bal and Kooij, 2011;Harpaz and Fu, 1997;Warr, 2008). For example, Mercure, Vultur and Fleury (2012) find that, among workers in Quebec, absolute and relative work centrality are the lowest among those with low educational attainment, the highest among those with post-secondary attainment and intermediate among those with academic degrees. Family centrality has been found to be negatively correlated with education (Kuchinke et al, 2011;Sharabi, 2000).…”
Section: Educationmentioning
confidence: 90%
“…This found a positive correlation between age and the importance attached to the life domains of family and work, and a negative correlation between age and leisure. Various studies have indeed shown that the older people get, the higher their work centrality (Bal and Kooij, 2011;Mercure, Vultur and Fleury, 2012;Kuchinke et al, 2009;Mannheim, Baruch and Tal, 1997;MOW, 1987;Sharabi and Harpaz, 2007;Warr, 2008). As noted above, Davoine and Méda (2010) found that in most European countries the young and middle generations see work as less important than do the older generations.…”
Section: Agementioning
confidence: 96%
See 2 more Smart Citations
“…La popularité grandissante des agences de location de main-d'oeuvre, souvent une porte d'entrée au marché du travail pour les jeunes, crée des conditions de travail différenciées qui se répercutent sur la santé et la sécurité du travail. De même, l'évolution du marché du travail et de l'emploi transformerait le rapport au travail chez des travailleurs d'âges différents et la « trajectoire professionnelle » (Mercure, Vultur et Fleury, 2012 En contexte de transition de la main-d'oeuvre (départ massif à la retraite et arrivée de nouveaux travailleurs), cette expertise de travail développée sur une longue période de temps, en fonction de la trajectoire professionnelle et de la trajectoire de santé, semble menacée (Cloutier, Ledoux et Fournier, 2012). De nouvelles études s'intéressent aujourd'hui, en situation réelle de travail, aux conditions facilitant ou non la transmission des savoirs entre les travailleurs expérimentés et les novices (Gaudart et Thébault, 2012;Ouellet, 2012;Laberge et al, 2012).…”
Section: La Variable âGe En Lien Avec D'autres Facteursunclassified